2022
DOI: 10.1038/s41467-022-30717-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic dissection of Klebsiella pneumoniae infections in hospital patients reveals insights into an opportunistic pathogen

Abstract: Klebsiella pneumoniae is a major cause of opportunistic healthcare-associated infections, which are increasingly complicated by the presence of extended-spectrum beta-lactamases (ESBLs) and carbapenem resistance. We conducted a year-long prospective surveillance study of K. pneumoniae clinical isolates in hospital patients. Whole-genome sequence (WGS) data reveals a diverse pathogen population, including other species within the K. pneumoniae species complex (18%). Several infections were caused by K. variicol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 84 publications
(125 reference statements)
12
105
0
Order By: Relevance
“…Both sequence clusters were found in each delivery cohort. Out of these, at least ST323 has been previously associated with ESBL carriage and nosocomial transmission [22].…”
Section: Resultsmentioning
confidence: 99%
“…Both sequence clusters were found in each delivery cohort. Out of these, at least ST323 has been previously associated with ESBL carriage and nosocomial transmission [22].…”
Section: Resultsmentioning
confidence: 99%
“…The opportunistic human and animal pathogen, causing pneumonia and urinary tract disease is Klebsiella pneumoniae (Martínez-Romero et al 2018;Rodriguez-Medina et al 2019, Gorrie et al 2022. Some strains of this bacterium cause plant diseases and some are defined as harmless or even beneficial plant endophytes (Rosenblueth et al 2004;Huang et al 2016;Duran-Bedolla et al 2021;Yang et al 2021).…”
Section: Bacterial Human Pathogens Occa-sionally Causing Plant Diseasesmentioning
confidence: 99%
“…The ICU substudy showed that the majority of K. pneumoniae infections in ICU patients (~ 80%) resulted from K. pneumoniae colonising the patients’ gut on admission to hospital, with < 20% of cases [ 14 ] resulting from nosocomial transmission. Analysis of the full collection of Alfred Health network clinical isolates reflected a similar pattern, estimating just 10% of K. pneumoniae infections resulted from nosocomial transmission [ 13 ]. Importantly ESBL carriage was the most significant risk factor for nosocomial transmission (OR 21, p < 1 × 10 −11 in a logistic regression model; estimated risk of onward transmission was 28% for ESBL strains vs 1.7% for non-ESBL strains), and transmission of ESBL strains was shown to be responsible for doubling the prevalence of ESBL + K. pneumoniae from 15% in the first 9 months of the study to > 30% in the final 3 months [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the full collection of Alfred Health network clinical isolates reflected a similar pattern, estimating just 10% of K. pneumoniae infections resulted from nosocomial transmission [ 13 ]. Importantly ESBL carriage was the most significant risk factor for nosocomial transmission (OR 21, p < 1 × 10 −11 in a logistic regression model; estimated risk of onward transmission was 28% for ESBL strains vs 1.7% for non-ESBL strains), and transmission of ESBL strains was shown to be responsible for doubling the prevalence of ESBL + K. pneumoniae from 15% in the first 9 months of the study to > 30% in the final 3 months [ 13 ]. The vast majority of acquired AMR genes amongst K. pneumoniae clinical infections was found to be plasmid-encoded, and the most common ESBL gene was bla CTX-M-15 ; however, plasmid transmission was not investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation